Sensory Profile of Jelly Yogurt Candy Pumpkin Juice (Cucurbita Moschata) - Della Purnamasari; Yenni Okfrianti; Desri Suryani (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study aims to produce an innovative product in the form of jelly candy made from pumpkin juice and yogurt. Pumpkin is rich in beta carotene and dietary fiber, while yogurt contains probiotics that are beneficial for digestive health. The combination of the two is expected to produce a functional food product with a pleasant taste and high nutritional value. Methodology: The study used an experimental method with various comparisons of pumpkin juice and yogurt. Product quality was assessed through descriptive tests including color, aroma, taste, and texture, while the level of panelist preference was tested hedonic. Data were analyzed using the Kruskal-Wallis test followed by Mann-Whitney. Results: The study showed that the formulation of 60 ml pumpkin juice: 40 ml yogurt (F4) obtained the highest level of preference with an average value of 3.88, while the formulation of 30 ml pumpkin juice: 70 ml yogurt (F7) had the lowest acceptance (3.23). The resulting product has a deep yellow color typical of natural pumpkin pigments and different sensory characteristics in each formulation. Findings: Confirms that the proportion of ingredients has a significant effect on the sensory quality and acceptability of the product. Novelty: This research utilizes pumpkin juice as the main ingredient in functional jelly candy, combined with yogurt as a source of probiotics. Originality: Development of a healthy, highly nutritious snack with commercial potential. Conclusion: Formulation F4 is the best choice for sensory acceptance. This research recommends further studies on nutritional content, shelf life, and broader consumer acceptance. Type of Paper: Research Article